Strategic Ignorance of Health Risk: Its Causes and Policy Consequences - Jonas Nordström; Linda Thunström; Klaas van 't Veld; Jason F. Shogren; Mariah Ehmke (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
We examine the causes and policy consequences of strategic (willful) ignorance of risk as an excuse to overengage in risky health behavior. In an experiment on Copenhagen adults, we allow subjects to choose whether to learn the calorie content of a meal before consuming it, and measure their subsequent calorie intake. We find strong evidence of strategic ignorance: 46% of subjects choose to ignore calorie information, and these subjects subsequently consume more calories on average than they would have had they been informed. We find that strategically ignorant subjects downplay the health risk of their preferred meal being high-calorie, which we formally show is consistent with the theory of optimal expectations about risk. Further, we find that the prevalence of strategic ignorance largely negates the effectiveness of calorie information provision: on average, subjects who have the option to ignore calorie information consume about the same number of calories as subjects who are provided no information.
Keywords: D11; D12; D81; D83; D91; I12; 330; strategic ignorance; willful ignorance; risk perception; optimal expectations; calories; information